Clinico-demographic Profile of Patients Presenting with Road Traffic Accidents at National Trauma Center of Nepal: An Observational Study - Badri Rijal; Bikash Kc; Amartya Dahal; Nabaraj Gautam; Min Chandra Adhikari (Journal of Nepal Medical Association, 2024)
Introduction: Road traffic accidents are a major global health concern, accounting for 1.35 million fatalities and countless impairments every year. The number of road traffic accidents in Nepal is rising, which has a significant effect on the country's economy and healthcare system. Over a period of five years, the study aimed to analyze the clinico-demographic characteristics of patients admitted for injuries due to road traffic accidents in the National Trauma Center of Nepal. Methods: This is an observational study conducted by reviewing a five-year admission data from 2018 to 2023 A.D. of a tertiary care trauma center. The study was conducted following approval from the Ethical Review Board of Nepal Health Research Council (Reference number: 969). All patients admitted to the trauma centre following injuries due to road traffic accidents were included in the study. The results were summarised using descriptive statistics. Results: Out of 20,843 admissions, 3,810 (18.28%) were due to RTAs. The male-to-female ratio was 4.44:1, with a median age of 31.00 (24.00 to 43.00) years. Age distribution was as follows: <18 years (6.75%), 18-39 years (62.13%), 40-59 years (23.62%), and ≥60 years (7.50%). The median hospital stay was 8.00 (3 to 16) days. The most common injuries were lower limb 2386 (62.62%), upper limb 958 (25.14%), and head injuries 890 (23.36%). The mortality rate was 72 (1.89%). Conclusions: Injuries due to road traffic accidents constitute a significant portion of admissions at the National Trauma Center in Nepal, predominantly affecting young males. Lower limb injuries were most common.